Performing Public Credit at the Eighteenth-Century Bank of England. (27th March 2019) - Murphy, Anne L.
Abstract: Much is known about the negotiation of personal credit relationships during the eighteenth century. It has been noted how direct contact and observation allowed individuals to assess the creditworthiness of those with whom they had financial connections and to whom they might lend money. Much less is known about one of the most important credit relationships of the long eighteenth century: that between the state and its creditors. This article shows that investors could experience the performance of public credit at the Bank of England. By 1760 the Bank was the manager of nearly three-quarters of the state's debt and housed the main secondary market in that debt. Thus, it provided a place for public creditors, both current and potential, to attend and scrutinize the performance of the state's promises. The article demonstrates how the Bank acted to embody public credit through its architecture, internal structures, and imagery and through the very visible actions of its clerks and the technologies that they used to record ownership and transfer of the national debt. The Bank of England, by those means, allowed creditors to interrogate the financial stability and reputation of the state in the same ways that they could interrogate the integrity of a private debtor.